Staphylococcus aureus-Specific Tissue-Resident Memory CD4+ T Cells Are Abundant in Healthy Human Skin - Hendriks, Astrid; Mnich, Malgorzata Ewa; Clemente, Bruna; Cruz, Ana Rita; Tavarini, Simona; Bagnoli, Fabio; Soldaini, Elisabetta (Frontiers in Immunology, 2021)
The skin is an immunocompetent tissue that harbors several kinds of immune cells and a plethora of commensal microbes constituting the skin microbiome. Staphylococcus aureus is a prominent skin pathogen that colonizes a large proportion of the human population. We currently have an incomplete understanding of the correlates of protection against S. aureus infection, however genetic and experimental evidence has shown that CD4+ T cells play a key role in orchestrating a protective anti-S. aureus immune response. A high S. aureus-specific memory CD4+ T cell response has been reported in the blood of healthy subjects. Since T cells are more abundant in the skin than in blood, we hypothesized that S. aureus-specific CD4+ T cells could be present in the skin of healthy individuals. Indeed, we observed proliferation of tissue-resident memory CD4+ T cells and production of IL-17A, IL-22, IFN-γ and TNF-β by cells isolated from abdominal skin explants in response to heat-killed S. aureus. Remarkably, these cytokines were produced also during an ex vivo epicutaneous S. aureus infection of human skin explants. These findings highlight the importance of tissue-resident memory CD4+ T cells present at barrier sites such as the skin, a primary entry site for S. aureus. Further phenotypical and functional characterization of these cells will ultimately aid in the development of novel vaccine strategies against this elusive pathogen.